ChemInform Abstract: A Photoreducible Copper(II)‐Tren Complex of Practical Value: Generation of a Highly Reactive Click Catalyst. Issue 19 (13th May 2014) - Harmand, Lydie; Lambert, Romain; Scarpantonio, Luca; McClenaghan, Nathan D.; Lastecoueres, Dominique; Vincent, Jean‐Marc
Abstract A detailed study on the photoreduction of a copper(II) precatalyst to generate a highly reactive cuprous species for the copper(I)‐catalyzed alkyne‐azide cycloaddition (CuAAC) click reaction is presented.